A contemporary theory of social entrepreneurship from Tawhidic paradigm: a conceptual study - Azan, Zaliza; Mhd. Sarif, Suhaimi (Human Resource Management Academic Research Society (HRMARS), 2017)
This study postulates a contemporary social entrepreneurship theory from Tawhidic paradigm for a comprehensive theory to describe the nature of the social entrepreneurship, the scope and boundaries of assessment on social entrepreneurship environments, and the assessment of internal aspects social entrepreneurship entities to formulate, implement, and evaluate strategies for survival and growth. The conventional approach to the theories of social entrepreneurship is not adequate to respond to external, internal, and human dynamism. The market-based theories of the social entrepreneurship emphasised on the market orientation of industrial organizational perspective only of the social entrepreneurship, which is lack of dynamism and sustainability for social entrepreneurship to survive and grow. As an alternative, this study postulates a social entrepreneurship theory of the firm the Tawhidic paradigm approach as a mean to achieve sustainability in terms of innovation and competitive advantages for social entrepreneurship. The study uses qualitative methods via (a) semi structured personal interview with three types of informants - government officers, SME association representatives, and founders/owners/managers of social enterprises in Malaysia, and a quantitative method via self-administered survey to social enterprises in Malaysia. The study expects the Tawhidic approach contributes to the theoretical and practical understanding of the development of a theory of social entrepreneurship. The results of the study should be considered tentative, or work-in-progress.